Prognostic significance of pyroptosis-associated molecules in endometrial cancer: a comprehensive immunohistochemical analysis - Ha, Seong-Chan; Park, Yeon Soo; Kim, Jisup (Frontiers in Oncology, 2024)
Introduction: Endometrial cancer, the most prevalent malignancy of the female genital tract, has a concerningly poor prognosis when diagnosed in advanced stages, with limited targeted therapy options available for advanced or recurrent cases. Pyroptosis, a type of nonapoptotic cell death mediated by caspase-1, has shown potential antitumor effects in various tumors. NLRP3, a cytosolic sensor, initiates the canonical pyroptotic pathway, leading to caspase-1 activation, subsequent gasdermin D cleavage, and plasma membrane pore formation. The ESCRT-III machinery, particularly CHMP4B, acts as a key inhibitor of pyroptosis by repairing gasdermin D-induced membrane damage. The current study aimed to evaluate the clinicopathologic relevance of key pyroptosis-associated molecules in endometrial cancer. Methods: Immunohistochemistry was used to assess the expression of four pyroptosis-associated molecules (NLRP3, cleaved caspase-1 p20, cleaved gasdermin D, and CHMP4B) in 351 patients with endometrial cancer, and their associations with clinical, pathological, and survival outcomes were analyzed. Results: High NLRP3 expression was significantly associated with age ≤ 50 years and premenopause. Increased cleaved caspase-1 p20 expression was associated with nonendometrioid carcinoma, Federation of Gynaecology and Obstetrics (FIGO) grade 3, and the p53 mutant pattern and was independently associated with poor recurrence-free survival (RFS) and overall survival. Increased cleaved gasdermin D expression was associated with a body mass index of >25 kg/m², FIGO grades 1–2, early FIGO stage (I–II), and absence of lymph node metastasis. High CHMP4B expression was associated with nonendometrioid carcinoma and poor RFS. Cleaved gasdermin D-high/CHMP4B-low endometrial cancer was associated with endometrioid carcinoma, FIGO grades 1–2 and favorable RFS. Discussion: Our study identified cleaved caspase-1 p20 as an independent predictor of adverse outcomes in endometrial cancer. CHMP4B, an inhibitor of pyroptosis, was associated with an unfavorable RFS, whereas high cleaved gasdermin D/low CHMP4B expression was associated with a favorable RFS. These findings underscore the prognostic significance of pyroptosis and the potential interaction between cleaved gasdermin D and CHMP4B in endometrial cancer.